Ética biocultural y cultura del maíz - Huante Raya, Tzivia Margarita (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
I analyze, from the perspective of environmental ethics, some of the cultural risks inherent in the model of modernization and technification of agriculture. In particular I focus in the challenges that the introduction of genetically modified corn seeds presents for important aspects of Mexican culture, traditionally centered around the production and consumption of maize. Based on the conceptual tools proposed in Ricardo Rozzi‘s biocultural ethics, I identify the following cultural risks, some of which have already become materialized: genetic and biocultural homogenization, dietary transformation, linguistic homogenization, rural-urban migration.

En este trabajo de investigación analizo, desde la ética ambiental, algunos de los riesgos culturales que conlleva el modelo de la modernización y tecnificación de la agricultura, enfocándome, en particular, en los riesgos que implica la introducción de semillas transgénicas para la cultura del maíz en México. Con base en la herramienta conceptual de la ética biocultural propuesta por Ricardo Rozzi, se identifican los siguientes riesgos, algunos de los cuales ya están materializados: homogenización genética y biocultural, transformación alimenticia, homogenización lingüística, y migración rural-urbana.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2015-1506; Cultura; Maíz transgénico; Homogenización; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/115